“TEN SPOONFULS MAKE A BOWL OF RICE”: AN INTRODUCTION TO KOREAN CULTURE WITH THE HELP OF ITS PROVERBS - Nolte, Andreas (Proverbium - Yearbook, 2011)
Korea is a rather unknown country and its proverbs are arguably not very well presented yet in paremiological research. Isolated from the West until only recently, the country’s unique culture and its rich traditions are still not very well known. As an important player on the world’s stage at the beginning of the 21st century, it is time for us to learn about Korea. This paper uses a selection of mostly older Korean proverbs to introduce certain aspects of Korean culture. Based on, and inspired by, a summer workshop in South Korea that the author attended in July 2010 with twelve other Vermont educators, the text introduces a selection of important Korean symbols, norms, and values and shows how these are reflected in the country’s proverbs. Using many examples from the handful of proverb collections available in translation, the text shows how looking at the proverbial language of a people can highlight and explain certain aspects of cultural identity. The selection of traditional wisdom provided here serves as a valuable and interesting window into the culture of Korea as well as an opportunity to get to know many unique Korean proverbs.